Design and Application of Led Driver Based on Isolated DC-DC Cuk Converter by Comparing Power Led Models - ŞEHİRLİ, Erdal (Omer Halisdemir Universitesi, 2023)
Design and application of led driver with isolated cuk converter for 10W is realized in this paper especially for automotive purposes. The advantage of isolated cuk topology than conventional Cuk topology is to have electrical isolation with supply and load and providing same polarity output. Besides, power led model including constant voltage and exponential models is obtained and employed in simulation study for comparison. Furthermore, maximum current limitation of power led is provided via dsPIC30f4011 microcontroller. Also, power switch is operated by 100 kHz switching frequency, and connection of the power led driver to the source provided by LC with parallel damping filter, whose noise reduction shown by application as well. With experimental set up, proving the desired results achieved by the converter, led current-voltage, input voltage-current are measured. Simulation results also verifies application. Moreover, exponential power led model provides more accurate results than constant voltage model.
Keywords: 7. Clean energy